КОМПЕТЕНТНІСНИЙ ПІДХІД У ПІДГОТОВЦІ МАЙБУТНІХ ВЧИТЕЛІВ ПОЧАТКОВИХ КЛАСІВ ДО ПРОФЕСІЙНОЇ ДІЯЛЬНОСТІ В НОВІЙ УКРАЇНСЬКІЙ ШКОЛІ - Романюк, Світлана (Київ: Міленіум., 2021)
The growth of the role and importance of pedagogical education in the preparation of a modern primary school teacher for the New Ukrainian School is substantiated. Discovered goal and task, substance and content, means of implementing a competent approach in the educational process of higher education institutions, which ensure the formation of the personnel potential of the primary school, have been revealed. It is characterized by the pedagogical competence of the expert and his professional functions in the future. There are specific problems with the working of the discharge chambers and specific ways to solve them.
Keywords: the competent approach, the new Ukrainian school, the primary teacher, professional competence, pedagogical education, the education process, the modernization of education, the key competences, pedagogical activity.